CARDIOPROTECTIVE ACTIVITIES OF QUERCETIN AND RUTIN IN SPRAGUE DAWLEY RATS TREATED WITH 5-FLUOROURACIL - E. Sengul1; V. Gelen; S. Gedikli (Journal of Animal and Plant Sciences, 2020)
In this study, the protective effects of Quercetin (Q) and Rutin in 5-fluorouracil (5-FU)-induced cardiotoxicity in rats were investigated and used eighty-piece Sprague Dawley male rats. Rats were divided randomly to eight groups; control, 5-FU, Q50+5-FU, Q100+5-FU, Q100, Rutin50+5-FU, Rutin100+5-FU, Rutin100. The control group was given intragastric (ig) corn oil for 14 days. 5-FU group was injected intraperitoneal (ip) with a single dose of 50 mg/kg. The doses of Q (50 and 100 mg/kg) and Rutin (50 and 100 mg/kg) were administered for 14 days. Rat of the 5-FU-administered groups were sacrificed under anesthesia 72 hours after 5-FU administration. The other groups were sacrificed on the day 15 after the administration. The blood samples were collected from anesthetized rats and sera were isolated from the clotted blood. The cardiac tissues were used for biochemical, histopathological and immunohistochemical analysis. Cardiac enzyme levels were significantly increased in the 5-FU group. Malondialdehyde (MDA) level was significantly higher than control in the 5-FU group and decreased in the Q100+5-FU and Rutin100+5-FU. Superoxide dismutase (SOD) and glutathione (GSH) activities were significantly decreased in the 5-FU group compared to the control, Q100+5-FU and Rutin100+5-FU. 5-FU groups had degeneration of cardiac cells and myofibril. The intensity of β-MHC positivity was higher in the 5-FU group compared to the other groups. In conclusion, this study demonstrates that Q (50 and 100 mg/kg) and Rutin (50 and 100 mg/kg) have protective effects on the 5-FU-induced cardiotoxicity in rats.
Keywords: 5-fluorouracil: Cardiotoxicity: Quercetin: Rutin: Rat